Kaizen for standardizing educational institutions - M, Nagaraja; K, Sivakumar; R, Sundaresan; S, Narayanan (Journal of Management and Science, 2012)
Teaching, scientific and technological innovations are the most important key factors and heart of an educational institute. It is necessary to monitor and focus the entire aspects of an institute to bring overall improvements. Effective teaching –learning process, quality, resource management and other improvement can be achieved in a short period of time using Kaizen. This is a Total Employee Involvement (TEI) technique which brings together all the employees of an organization right from top management to workers for bringing continuous improvement in an academic organization.